Penerapan Teknologi Artificial Inteligence Dalam Mengoptimalkan Kemampuan Belajar Siswa Sekolah Dasar - Nasution, Arina Aghniya; Nasution, Cahaya; Rambe, Seri Mawardah (Journal of Sustainable Education, 2025)
The use of Artificial Intelligence (AI) technology in education has brought about significant transformations in learning methods, evaluation, and classroom management, especially at the elementary school level. This study aims to analyze the impact of implementing AI as a learning medium on improving the learning abilities of elementary school students. Through a qualitative descriptive approach, this study explores how AI can support adaptive, personal, and interactive learning. The results of the discussion show that AI provides convenience in conducting real-time learning evaluations, adjusting materials to student needs, and helping teachers monitor learning progress systematically. On the other hand, the application of AI also faces a number of challenges, such as the risk of dehumanizing the learning process, the gap in access to technology, and ethical issues of data privacy. Therefore, the integration of AI in elementary education must be carried out wisely and collaboratively, while maintaining the central role of teachers as the main guides in the learning process. In conclusion, AI has great potential in improving the quality of elementary education, but its success depends on the readiness of the education system, regulations, and ethics that accompany it.